Energy analysis and comparative study of n-wheel graphs in hierarchical wireless sensor network architectures - Jerlinkasmir Rubancharles; Naseema Valiyaveettil Abdul Lathief; Veninstine Vivik Joseph (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
The energy analysis of the newly introduced n-wheel graph, employs diverse matrix representations such as the adjacency matrix, Laplacian matrix, and maximum degree matrix. This novel graph model resembles a hierarchical wireless sensor network (WSN), with a central hub serving as the communication center. The graph is organized into cycles, reflecting tiers of devices or sensors, with the hub managing wireless communication across these tiers. Through comparative analysis of energy variations, particularly focusing on ordinary energy, Laplacian energy, and maximum degree energy, offers a deeper understanding on the potential benefits of the n-wheel graph model, guiding future research and practical applications in the design of advanced hierarchical network structures.